The shape of water - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2002)
The first English translation of the best-selling international mystery series follows Sicilian detective Inspector Montalbano as he investigates the suspicious death of an engineer who had made a name for himself in a small town.